2009
DOI: 10.1128/jvi.00986-09
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Grown in Vero Cells Contains a Truncated Attachment Protein That Alters Its Infectivity and Dependence on Glycosaminoglycans

Abstract: Human respiratory syncytial virus (RSV) contains a heavily glycosylated 90-kDa attachment glycoprotein (G). Infection of HEp-2 and Vero cells in culture depends largely on virion G protein binding to cell surface glycosaminoglycans (GAGs). This GAG-dependent phenotype has been described for RSV grown in HEp-2 cells, but we have found that it is greatly reduced by a single passage in Vero cells. Virions produced from Vero cells primarily display a 55-kDa G glycoprotein. This smaller G protein represents a post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
101
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(112 citation statements)
references
References 53 publications
7
101
2
2
Order By: Relevance
“…However, the G protein is cleaved in only a few cell lines (12). One reason for this difference is that cathepsin L activity is much lower in HeLa cells than in Vero cells (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…However, the G protein is cleaved in only a few cell lines (12). One reason for this difference is that cathepsin L activity is much lower in HeLa cells than in Vero cells (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…The first indication that Vero cell-derived RSV was different from HEp-2 cell-derived RSV came when we found that HEp-2 cell-derived virus was 20-fold more infectious than Vero cell-derived virus for CHO cells that express HS than for CHO cells that are deficient in HS production (12). This finding prompted us to examine the G protein in virions, and we found that most of it was 55 kDa rather than 90 kDa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations